Analysing the potential of serious games to raise new research questions on social-ecological systems - Lombard Latune Julie; Berthet Elsa T.; Fouqueray Timothée; Souchère Véronique; Frascaria-Lacoste Nathalie (Natures Sciences Sociétés)
As transdisciplinary approaches are increasingly required to study social-ecological systems (SES) and address the complex relationships between humans and nature, this paper explores the potential of serious games (SG) as tools that can help researchers in formulating new research questions. We draw on a comparative case study of six SG to explore the extent to which these games can facilitate the generation of new research questions on SES. We highlight three key potential properties of these tools: enabling researchers to identify (i) knowledge gaps, (ii) mismatches between theoretical expectations and observations (‘anomalies’), and (iii) overlooked social-ecological interactions, which can change the researchers’ representations of the systems under study. Our comparative study shows that SG have the capacity to generate novel research questions that integrate both people and nature within social-ecological systems.